PRECISA-SE DE PROFESSOR DINÂMICO - Teles, Carla Xavier; Fausto, Fabiana Macedo (Intercâmbio, 2010)
What makes a “dynamic” teacher? The uncertainty concerning this adjective led us to investigate it in the opinion of the following groups: students, teachers and coordinators of EFL courses. The collected data were analyzed both qualitatively and quantitatively by means of the statistical program SPSS.